The Effects and Challenges of Integrating GoAnimate Video Creator with TaskBased Language Teaching (TBLT) in Teaching English to a Grade 11 Omani Class - Al Khalili, Shatha (2018)
This qualitative research explores the effects and challenges of integrating the GoAnimate web-based tool with task-based language teaching (TBLT) in teaching writing to a grade 11 EFL, Omani classroom. The literature review covers specific topics that form the basis of TBLT, such as constructivism, cooperative learning, group dynamics and the affective filter hypothesis. Moreover, it introduces GoAnimate and brings to light some current multimodality related studies as GoAnimate is part and parcel of it. When it comes to the methodology, convenience sampling is adopted and thus, the sample consists of 6 teachers and 34 students. Additionally, the instrument used to collect data is students’ and teachers’ focus group interviews and the researcher’s self-observational notes. Furthermore, the procedure involves designing a female GoAnimate character called ‘Awash’ and using her to teach a writing lesson while the researcher observes and takes notes. After the lesson, the focus group interviews are conducted. After that, the gathered data is analysed and the research questions are answered. The findings of this research indicate that the integration of GoAnimate in the Omani classroom faces some challenges. Nevertheless, those challenges can be overcome if addressed properly. Additionally, the findings highlight that GoAnimate has a positive effect on students’ motivation and thus, their learning. Based on these findings, some implications for practice and research are put forward.